Underdog Advertising® : Proven Principles to Compete and Win Against the Giants in Any Industry. (Electronic & Database Publishing Inc., 2006)
'Underdog Advertising'® is written for the small-to-mid size business owner/operator who cannot afford to hire an advertising agency. The book presents principles and processes that have proven successful for advertisers who must compete with larger companies in their industries for sales, awareness and market share. 'Underdog Advertising' has four primary components and just as David toppled Goliath with a well-aimed rock, the disciplines introduced in this book have consistently helped "budget underdogs" hit the mark and become the real winners. It may be just the weapon you need.